2000
DOI: 10.21273/jashs.125.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Strawberry Root System Traits in Fumigated and Nonfumigated Soils I. Inheritance Patterns of Strawberry Root System Characteristics

Abstract: Seedling offspring of crosses among 10 selected strawberry genotypes (Fragari ×ananassa Duch.) from the University of California strawberry improvement program were established in annual hill culture. Soil treatments consisted of 1) preplant fumigation using a mixture of methyl bromide and chloropicrin or 2) no fumigation. Root systems of individual plants were sampled with a soil probe in January, April, and July 1994 to determine root mass (RM), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Although breeding and subsequent development of specially adapted cultivars is cited frequently as an alternative to preplant soil fumigation for strawberry (USDA, 1993;Watson et al, 1992), studies published to date have demonstrated a virtual absence of genetic variance for specific adaptation to the sublethal soil organisms that affect strawberry performance. This general absence of soil-specific adaptive variation is evidenced by the nonsignificant genetic × fumigation interactions found in California germplasm for production traits (Fort and Shaw, 2000 b;Fort et al, 1996;Larson and Shaw, 1995) and root characteristics (Fort and Shaw, 2000a). Soil-specific adaptive variation was also absent in studies that included other North American germplasm sources of F. ×ananassa , and when fumigation responses were evaluated in perennial strawberry cultural systems (Hancock et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Although breeding and subsequent development of specially adapted cultivars is cited frequently as an alternative to preplant soil fumigation for strawberry (USDA, 1993;Watson et al, 1992), studies published to date have demonstrated a virtual absence of genetic variance for specific adaptation to the sublethal soil organisms that affect strawberry performance. This general absence of soil-specific adaptive variation is evidenced by the nonsignificant genetic × fumigation interactions found in California germplasm for production traits (Fort and Shaw, 2000 b;Fort et al, 1996;Larson and Shaw, 1995) and root characteristics (Fort and Shaw, 2000a). Soil-specific adaptive variation was also absent in studies that included other North American germplasm sources of F. ×ananassa , and when fumigation responses were evaluated in perennial strawberry cultural systems (Hancock et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Spangelo et al (1971) indicated the low heritability of fruit firmness and the ease of calyx removal, caused by a large share of non-additive variation in the total genetic variation of these traits. Detailed information about which genetic effects (additive or non-additive) predominantly determine a given trait in the progeny is also provided by the quotient of mean square deviations for GCA and SCA (S GCA 2 /S SCA 2 ) (MacLachlan 1978;Fort and Shaw 2000). A high value of this quotient for a trait indicates that the trait is mostly genetically controlled by additive effects within a reference population.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, knowledge of the specific combining ability (SCA) of a pair of parental forms (which is a genetic interaction of both parents as a result of nonadditive gene action (dominance and epistasis), showing in their offspring -Griffing 1956a, b), in respect of the trait under consideration, allows for an examination of the differences between the value of the revealed trait and the value expected on the basis of the sum of GCA effects for those parental forms (Bestfleisch et al 2014). The quotient of the mean square deviations for GCA and SCA (S GCA 2 /S SCA 2 ) provides for the determination of which genetic effects (additive or non-additive) have a predominant share in determining a given trait in the tested progeny (Fort and Shaw 2000).…”
Section: Introductionmentioning
confidence: 99%